A Magyar Néphadsereg . The Hungarian People's Army - írta: Domokos József ; szerkesztette: Szécsi András. (Magyar Diafilmgyártó Vállalat, 1971)
Produced in cooperation with the Hungarian People's Army Financial and Methodological Centre for Political Education. Készült a Magyar Néphadsereg Politikai Nevelőmunka Anyagi és Módszertani Központja gondozásában.